Strengthening Science Literacy Framework 2025 through the TPACK-P Framework for Science Teachers - Insih Wilujeng; Desy Purwasih; Marinda Noor Fajrina Noviana Putri; Susilowati Susilowati (Universitas Lambung Mangkurat, 2026)
The implementation of TPACK-P faces several challenges, including limitations in utilizing technology that aligns with the science curriculum based on scientific literacy, a lack of continuous professional training for teachers, and the need to adapt teaching methods to accommodate students’ multicultural backgrounds. Therefore, efforts are needed to strengthen TPACK-P through intensive training and research-based practice to enhance Science Literacy 2025 and improve the effectiveness of science learning. The method in this study used training or workshops. The implementation mechanism of this community service program consists of three stages: preparation, implementation, and evaluation. The training activities were conducted through direct workshops with participants from Sekolah Indonesia Kuala Lumpur in Malaysia and science teachers in Yogyakarta. Data on teachers’ experiences in using TPACK-P were collected using instruments distributed via Google Forms and analyzed using a descriptive qualitative approach. The results showed that 96% of teachers possessed knowledge related to TPACK-P, while only 88% had classroom experience applying it. This indicates that the training provided teachers with valuable hands-on experience in using TPACK-P to design science learning